Criminal Liability Against Livestock Owners That Damage Other People's Gardens - Achmad Surya; Suhartini Suhartini (JURNAL BELO, 2022)
In criminal law, owners who allow their livestock to damage other people's land or gardens can be held legally responsible, as regulated in Article 549, paragraph 1 of the Criminal Code. However, in practice in the field, there are still people who keep their livestock in other people's gardens. This study aims to examine criminal sanctions against livestock owners who damage other people's gardens and criminal liability for those who damage other people's gardens. This type of research is juridical empirical by using primary data and secondary data. The results show that Criminal sanctions against livestock owners who enter other people's gardens may be subject to fines or compensation for parks damaged by livestock. If the penalties are not implemented, they can be replaced with imprisonment for 14 (fourteen) days. At the same time, criminal liability to livestock owners who enter other people's gardens can only be resolved amicably or peacefully at the village level through the traditional sarak opat institution.